CHARACTERIZATION OF LIFEPO4 BATTERY CATHODE MATERIALS SYNTHESIZED BY CO- PRECIPITATION METHOD USING FEPO4 PRECURSORS AT VARIATIONS OF PH, CARBON ADDITION, AND SINTERING TEMPERATURE - Dzikri Robbani, Farhan
Electric vehicles are a form of environmentally friendly vehicle innovation, most of which use batteries as energy storage. Research and development on batteries continues to be carried out in order to obtain a type of battery that has a high efficiency, environmentally friendly, and economically competitive. This research is focused on studying the synthesis of LFP by co-precipitation method using commercially available FePO4 precursors. The product’s characteristics of the synthesized LFP cathode material with variations in precipitation pH, addition of carbon, and the effect of variations in sintering temperature were studied which can produce an olivine phase with small particle size, good crystallinity, and morphology. A series of experiments were carried out with the addition of carbon prior to the drying process using carbon black. The experiments were carried out at various pH of 4.5, 6.5, 8.5, and 10.5, as well as sintering temperature variations of 650 °C, 700 °C and 750 °C. The resulting product was then characterized using X-ray diffraction (XRD) to identify the phase formed, the crystallinity, and the size of the crystallites. Analysis with a scanning electron microscope (SEM) was performed to determine the morphology of the synthesized LFP material, while the particle size analysis of the LFP product was carried out with a PSA (particle size analyzer). The conditions of precipitation pH and sintering temperature were determined which produced the best product which formed the olivine phase. Furthermore, the conditions of precipitation pH and sintering temperature that produce the best product are used to vary the addition of carbon for determining the effect of adding carbon on the characteristics of the product obtained. The experimental results show that the precipitation reaction of the LFP product occurs in the pH range of 4.5-8.5. Average yield of precipitation products produced at pH 4.5, 6.5, 8.5, and 10.5 were 86.53%, 67.54%, 66.05% and 0%, respectively. At a precipitation pH of 4.5–8.5, a nasicon phase mixed with an unwanted diphosphate phase was produced, whereas at a pH of 6.5 a nasicon phase mixed with the targeted olivine phase was formed. The addition of carbon contributed significantly to the formation of nasicon and olivine phases in the synthesized of LFP as a reducing agent to reduce iron(III) ions to iron(II). Analysis of the XRD results also showed that pH 6.5 with a sintering temperature of 700 °C gave the best results which produced a mixture of nasicon and olivine. Under these conditions a relative Fe:P mole ratio of 1:1 was obtained with a homogeneous spherical morphology and an average particle size of 351.06 nm.